Mestizo imaginaries of languages in contact in Latin America - López García-Molins, Ángel (2023)
Language contact, although it can be described with the same scientific asepsis as languages considered in themselves, is not a subject alien to the sensitivities of the speakers of the languages that came to share the same space. In this article, different theoretical issues related to this contrast are researched and exemplified with an analysis of the contact of Spanish with Amerindian languages in different areas of America, especially in Peru. Among the aspects dealt with are the prototype theory models that underlie the development of regulatory proposals, the question of language and dialect, a topological analysis of contact situations and the problem of multilingualism in its manifestations in the imaginary of peoples.